Association of endocrine disrupting chemicals levels in serum, environmental risk factors, and hepatic function among 5- to 14-year-old children. (15th January 2022) - Fu, Xiangjun; He, Jie; Zheng, Deliang; Yang, Xuefeng; Wang, Pan; Tuo, FangXu; Wang, Lin; Li, Shixu; Xu, Jie; Yu, Jie
Graphical abstract: Highlights: Association between serum EDCs level and risk factors among 5−14 year old children. Association in serum NP、BPA、DMP levels and hepatic function. Serum EDCs level in school-age children was highest in industrial zone. Differences in EDCs level and hepatic function in terms of sex and geographic area. Abstract: Endocrine-disrupting chemicals (EDCs) might increase the risk of childhood diseases by disrupting hormone-mediated processes that are critical for growth and development during childhood, however, the association among the exposure level of EDCs such as Nonylphenol (NP), Bisphenol A (BPA), Dimethyl phthalate (DMP) in children and environmental risk factors, as well as hepatic function has not been elaborated. This study aimed to discuss this interesting relationship among NP, BPA, DMP concentrations in serum, environmental risk factors, hepatic function of 5- to 14-year-old children in industrial zone, residential zone and suburb in northern district of Guizhou Province, China. In Zunyi city, 1006 children participated in cross-sectional health assessments from July to August 2018, and their parents completed identical questionnaires on the environmental risk factors of EDCs exposure to mothers and children. Serum NP, BPA and DMP concentrations were measured by high performance liquid chromatography (HPLC). Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), AST/ALT, total bilirubin (TBIL), direct bilirubin (DBIL) and indirect bilirubin (IBIL) were detected with automatic biochemical analyzer. The median concentrations of serum NP, BPA, and DMP in the participants were 45.85 ng/mL, 26.31 ng/mL and 31.62 ng/mL, respectively, which were higher than the environmental concentration limits of the U.S. National Environmental Protection Agency (EPA). Hair gels used during pregnancy, types of domestic drinking water, nail polish and cosmetics used by children were significantly positive correlated with serum NP concentration ( P < 0.05). Gender, feeding pattern, plastic water cup used during pregnancy, hair spray and perfume use for children, duration of children birth, materials for baby bottle or cup and ways to plastic products were significantly positively correlated with serum BPA concentration ( P < 0.05). Gender, perms used during pregnancy, hair spray and perfume use for children, using plastic lunch box during pregnancy, duration of children birth, exposure to pesticides, parents' occupations were significantly positively correlated with serum DMP concentrations ( P < 0.05). Serum NP ( β  = 0.296, P = 0.036) and DMP ( β  = 0.316, P = 0.026) concentrations and TBIL level were significantly positively correlated. Serum NP concentration and the levels of IBIL ( β  = 0.382, P = 0.006) are significantly positively correlated. Cosmetics used during pregnancy significantly increased AST level ( β  = 2.641, P = 0.021). There was a positive correlation between the frequency of hair spray and perfume use for children and the AST ( β  = 4.241, P = 0.022). NP, BPA and DMP, which were commonly detected in the serum of children aged 5−14 years old in Zunyi City, Northern Guizhou Province, China, were closely related to the environmental risk factors of exposure environment during pregnancy, infancy and school age. Exposure to NP, BPA and DMP would have negative effects on hepatic function, and these effects showed differences in gender and geographical location. Notably, The relationships were more evident in girls than in boys.